Cell-seeded alginate hydrogel scaffolds promote directed linear axonal regeneration in the injured rat spinal cord. (November 2015) - Günther, Manuel Ingo; Weidner, Norbert; Müller, Rainer; Blesch, Armin
Graphical abstract: Abstract: Despite recent progress in enhancing axonal growth in the injured spinal cord, the guidance of regenerating axons across an extended lesion site remains a major challenge. To determine whether regenerating axons can be guided in rostrocaudal direction, we implanted 2 mm long alginate-based anisotropic capillary hydrogels seeded with bone marrow stromal cells (BMSCs) expressing brain-derived neurotrophic factor (BDNF) or green fluorescent protein (GFP) as control into a C5 hemisection lesion of the rat spinal cord. Four weeks post-lesion, numerous BMSCs survived inside the scaffold channels, accompanied by macrophages, Schwann cells and blood vessels. Quantification of axons growing into channels demonstrated 3–4 times more axons in hydrogels seeded with BMSCs expressing BDNF (BMSC–BDNF) compared to control cells. The number of anterogradely traced axons extending through the entire length of the scaffold was also significantly higher in scaffolds with BMSC–BDNF. Increasing the channel diameters from 41 μm to 64 μm did not lead to significant differences in the number of regenerating axons. Lesions filled with BMSC–BDNF without hydrogels exhibited a random axon orientation, whereas axons were oriented parallel to the hydrogel channel walls. Thus, alginate-based scaffolds with an anisotropic capillary structure are able to physically guide regenerating axons. Statement of Significance: After injury, regenerating axons have to extend across the lesion site in the injured spinal cord to reestablish lost neuronal connections. While cell grafting and growth factor delivery can promote growth of injured axons, without proper guidance, axons rarely extend across the lesion site. Here, we show that alginate biomaterials with linear channels that are filled with cells expressing the growth-promoting neurotrophin BDNF promote linear axon extension throughout the channels after transplantation to the injured rat spinal cord. Animals that received the same cells but no alginate guidance structure did not show linear axonal growth and axons did not cross the lesion site. Thus, alginate-based scaffolds with a capillary structure are able to physically guide regenerating axons.